Educational Board Games vs Flashcards: Which One is More Effective to Teach Speaking Skills? - Dini Indriyani; Sundari Purwaningsih; Deni Chandra (Journal of Applied Linguistics (ALTICS), 2024)
language. However, there are schools that cannot afford to use digital media because the facilities are limited. To support learning English foreign language, non-digital media is still used in this technology era. This research examined the students who use educational board games achieve better speaking skills than those who use flashcards. This research was in a quasi-experimental design, participants included two eighth-grade classes from three classes of a junior high school which were randomly assigned to two groups. Thirty-two students were assigned to the experimental group taught with educational bord games and 32 students to the control group taught with flashcards. Tests prior to and after the speaking class were administered to the participants in both groups to measure their speaking performance. The result from pre-test and post-tests revealed that students who use educational board games achieve better speaking skills than those who use flashcards. The findings lend support to the possibility of exploring non digital media as effective teaching tools means to facilitate EFL learners in technology era.